Effect of Selected Metal Contaminants on the Stability of Castor Oil Methyl Ester. (28th January 2014) - Akhabue, Christopher E.; Iworah, John C.; Aisien, Felix A.
Abstract : This study investigates the effect of iron (Fe) and aluminium (Al) contaminants on the stability of castor oil methyl ester (COME). COME was synthesized via transesterification reaction and the peroxide value of the COME was used to monitor its stability. Varied amounts of Fe and Al (0.2 g, 0.4 g, 0.6 g, 0.8 g, and 1.0 g) in powdered form were added to 100 mL of COME and their effect on the peroxide value was monitored for a day, for the first phase of the experiment, while for the second phase, 0.3 g and 0.8 g of these metals were added to 100 mL COME, and their effect was monitored for 9 days. At the end of the study, it was observed that as the amount of the metals added to the COME increases from 0.2 to 1.0 g/100 mL COME, the peroxide values of the COME decrease from 1.6 to 0.3 meq/kg and 1.2 to 0.3–0.2 meq/kg for Al and Fe contaminated COME after 24 h. Also in the second phase of the experiment, the peroxide value of the 0.3 g Fe metal contaminated COME increased from 1.4 to 11.6 meq/kg while that of 0.8 g Fe contaminated COME increased from 1.4 to 3.0 meq/kg after the nine-day period of investigation.